Regulation of the Drosophila bHLH-PAS protein Sima by hypoxia: functional evidence for homology with mammalian HIF-1 alpha. - Bacon, N; Wappner, P; O'Rourke, J; Bartlett, S; Shilo, B; Pugh, C; Ratcliffe, P (1998)
Hypoxia inducible factor-1 (HIF-1) is a heterodimeric complex of two basic-helix-loop-helix proteins of the PAS family which is critical for oxygen-dependent expression of many mammalian genes. Regulation is mediated by the alpha subunit (HIF-1 alpha) and sequences from HIF-1 alpha can confer hypoxia-inducible activity on a Ga14 fusion protein. To analyse conservation of this system of gene regulation between Drosophila and mammalian cells we constructed Ga14 fusions with a series of Drosophila basic-helix-loop-helix PAS (bHLH-PAS) proteins and tested for hypoxia inducibility in transfected Hep3B cells. We found that Ga14 functions with Similar (Sima) but not other Drosophila bHLH-PAS proteins showed inducible activity following exposure to stimuli which classically activate mammalian HIF-1:hypoxia, cobaltous ions, and desferrioxamine. We also found that Sima protein accumulated in Drosophila SL2 cells following hypoxia. Together these findings indicate the existence of functional homologies between Sima and HIF-1 alpha, and that conservation is such as to enable Sima to interact with the hypoxia signal transduction system in mammalian cells.